COVID-19 as a mediator of interferon deficiency and hyperinflammation: Rationale for the use of JAK1/2 inhibitors in combination with interferon. (August 2021) - Hasselbalch, H.C.; Skov, V.; Kjær, L.; Ellervik, C.; Poulsen, A.; Poulsen, T.D.; Nielsen, C.H.
Graphical abstract: Highlights: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) elicits an interferon (IFN) deficiency state. Early treatment with IFN-alpha2 or IFN-beta, preferentially in the early disease stage, may prohibit disease progression. SARS-CoV-2 may also elicit a cytokine storm, which accounts for disease progression. JAK1/2 inhibitor treatment with ruxolitinib or baricitinib may decrease mortality by dampening the deadly cytokine storm. Combination therapy with IFNs and JAK1/2 inhibitor is proposed as a novel and rational treatment modality to be tested in clinical trials. Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) elicits an interferon (IFN) deficiency state, which aggravates the type I interferon deficiency and slow IFN responses, which associate with e.g. aging and obesity. Additionally, SARS-CoV-2 may also elicit a cytokine storm, which accounts for disease progression and ultimately the urgent need of ventilator support. Based upon several reports, it has been argued that early treatment with IFN-alpha2 or IFN-beta, preferentially in the early disease stage, may prohibit disease progression. Similarly, preliminary studies have shown that JAK1/2 inhibitor treatment with ruxolitinib or baricitinib may decrease mortality by dampening the deadly cytokine storm, which – in addition to the virus itself - also contributes to multi-organ thrombosis and multi-organ failure. Herein, we describe the rationale for treatment with IFNs (alpha2 or beta) and ruxolitinib emphasizing the urgent need to explore these agents in the treatment of SARS-CoV-2 – both as monotherapies and in combination. In this context, we take advantage of several safety and efficacy studies in patients with the chronic myeloproliferative blood cancers (essential thrombocythemia, polycythemia vera and myelofibrosis) (MPNs), in whom IFN-alpha2 and ruxolitinib have been used successfully for the last 10 (ruxolitinib) to 30 years (IFN) as monotherapies and most recently in combination as well. In the context of these agents being highly immunomodulating (IFN boosting immune cells and JAK1/2 inhibitors being highly immunosuppressive and anti-inflammatory), we also discuss if statins and hydroxyurea, both agents possessing anti-inflammatory, antithrombotic and antiviral potentials, might be inexpensive agents to be repurposed in the treatment of SARS-CoV-2.